Impaired Expression of Neuregulin 1 and Nicotinic Acetylcholine Receptor β4 Subunit in Diverticular Disease - Barrenschee, Martina; Cossais, François; Böttner, Martina; Egberts, Jan-Hendrik; Becker, Thomas; Wedel, Thilo (Frontiers in Cellular Neuroscience, 2019)
Neuregulin 1 (NRG1) regulates the expression of the nicotinic acetylcholine receptor (nAChR) and is suggested to promote the survival and maintenance of the enteric nervous system (ENS), since deficiency of its corresponding receptor complex ErbB2/ErbB3 leads to postnatal colonic aganglionosis. As diverticular disease (DD) is associated with intestinal hypoganglionosis, the NRG1-ErbB2/ErbB3 system and the nAChR were studied in patients with DD and controls. Samples of tunica muscularis of the sigmoid colon from patients with DD (n=8) and controls (n=11) were assessed for mRNA expression of NRG1, ErbB2 and ErbB3 and the nAChR subunits α3, α5, α7, β2 and β4. Site-specific gene expression levels of the NRG1-ErbB2/3 system were determined in myenteric ganglia harvested by laser microdissection. Localization studies were performed by immunohistochemistry for the NRG1-ErbB2/3 system and nAChR subunit β4. Rat enteric nerve cell cultures were stimulated with NRG1 or GDNF for 6 days and mRNA expression of the aforementioned nAchR was measured. NRG1, ErbB3 and nAChR subunit β4 expression was significantly down-regulated in both the tunica muscularis and myenteric ganglia of patients with DD compared to controls, whereas mRNA expression of ErbB3 and nAChR subunits β2, α3, α5 and α7 remained unaltered. NRG1, ErbB3 and nAChR subunit β4 immunoreactive signals were reduced in neuronal somata and the neuropil of myenteric ganglia from patients with DD compared to control. nAChR subunit β4 exibited also weaker immunoreactive signals in the tunica muscularis of patients with DD. NRG1 treatment but not GDNF treatment of enteric nerve cell cultures significantly enhanced mRNA expression of nAchR β4. The down-regulation of NRG1 and ErbB3 in myenteric ganglia of patients with DD supports the hypothesis that intestinal hypoganglionosis observed in DD may be attributed to a lack of neurotrophic factors. Regulation of nAChR subunit β4 by NRG1 and decreased nAChR β4 in patients with DD provide evidence that a lack of NRG1 may affect the composition of enteric neurotransmitter receptor subunits thus contributing to the intestinal motility disorders previously reported in DD.